In vivo administration of quercetin ameliorates sperm oxidative stress, inflammation, preserves sperm morphology and functions in streptozotocin-nicotinamide induced adult male diabetic rats - Yelumalai, Suseela; Giribabu, Nelli; Karim, Kamarulzaman; Omar, Siti Zawiah; Salleh, Naguib (Termedia Publishing House, 2019)
Introduction: Diabetes mellitus (DM) has been associated with sperm damage. In view of the fact that quercetin possesses antioxidant and anti-inflammatory activities, this compound may help to protect sperm against damage in DM. In this study, in-vivo effects of quercetin on sperm parameters in DM were investigated. Material and methods: Quercetin (10, 25 and 50 mg/kg/b.w.) was given orally to streptozotocin-nicotinamide induced adult male diabetic rats for 28 days. Following treatment completion, rats were sacrificed and sperm were harvested from the cauda epididymis. Sperm count, motility, viability, hyperosmotic swelling (HOS) tail-coiled sperm and morphology were assessed. Levels of lipid peroxidation (LPO) and anti-oxidative enzymes (SOD, CAT and GPx) in sperm with and without H 2 O 2 incubation were determined by biochemical assays. Expression levels of SOD, CAT and GPx mRNAs in sperm were evaluated by qPCR. Sperm DNA integrity was estimated by flow cytometry while expression levels of the inflammatory markers NF-κβ and TNF-α in sperm were determined by Western blotting. Results: In diabetic rats receiving quercetin, sperm count and motility, viability and HOS tail-coiled sperm increased (p < 0.05) while sperm with abnormal morphology decreased. Moreover, sperm SOD, CAT, GPx activities and their mRNA expression levels increased while sperm LPO, NF-κβ and TNF-α levels decreased. In normal and diabetic rat sperm incubated with H 2 O 2 , a further increase in MDA and further decreases in SOD, CAT and GPx were observed, and these were ameliorated by quercetin treatment. Conclusions: In-vivo administration of quercetin to diabetic rats helps to ameliorate sperm damage and improves sperm morphology and functions in DM.